A new history of management - Cummings, Stephen; Bridgman, Todd (Cambridge : Cambridge University Press, 2017)
Existing narratives about how we should organize are built upon, and reinforce, a concept of 'good management' derived from what is assumed to be a fundamental need to increase efficiency. But this assumption is based on a presentist, monocultural, and generally limited view of management's past. A New History of Management disputes these foundations. By reassessing conventional perspectives on past management theories and providing a new critical outline of present-day management, it highlights alternative conceptions of 'good management' focused on ethical aims, sustainability, and alternative views of good practice. From this new historical perspective, existing assumptions can be countered and simplistic views disputed, offering a platform from which graduate students, researchers, and reflective practitioners can develop alternative approaches for managing and organizing in the twenty-first century.
Machine generated contents note: 1. Rethinking the map of management history; 2. Management's formation: the importance of the liberal context; 3. To what end? The nature of management's classical approach; 4. The birth of organization science: or what we could learn from Max Weber; 5. The institution of the business school; 6. The discovery of the human worker; 7. Textbook distortions: how management textbooks process history and limit future thinking; 8. The invention of corporate culture; 9. Remaking management history: new foundations for the future.
Title from publisher's bibliographic system (viewed on 15 Sep 2017).
Keywords: elektronické knihy; electronic books; Management -- History; Organizational behavior